Investigation of the molecular interactions between β-lactoglobulin and low methoxyl pectin by multi-detection High Performance Size Exclusion Chromatography. (February 2017) - Qi, Phoebe X.; Chau, Hoa K.; Fishman, Marshall L.; Wickham, Edward D.; Hotchkiss, Arland T.
Abstract: To achieve controlled physiochemical, structural, and consequently, functional properties of interacting systems containing β-lactoglobulin (βLG) and commercial standardized low methoxyl pectin (LMP, DE 36.8%), solution conditions were established and studied at the weight ratio of 3:1 (w/w), pH ∼6.50. Online multi-detection High Performance Size Exclusion Chromatography (HPSEC) was used to characterize the physicochemical properties of the interacting biopolymer fractions in detail. Results showed that upon direct mixing, ∼6.1% (w/w) of native dimeric βLG molecules formed complexes with LMP molecules of two sizes, namely [Mw ] ∼ 250 and 55 kDa. The interactions produced complexes of altered shapes and hydrodynamic properties compared to those of βLG and LMP controls. Heat-induced (80 °C, 10 min) denaturation of βLG greatly increased its participation in the complexes as aggregates, to ∼10.4%, which appear to favor the LMP molecules of higher [Mw ]. Pre-heating LMP, however, impeded its binding to βLG and increased the amount of unbound βLG as a result. The effect of sucrose on the interactions between βLG and LMP was also investigated using a set of similarly treated samples but with sucrose removed from LMP. These studies demonstrated that sucrose greatly facilitated the complex formation, notably between the pre-heated βLG and LMP. The structures of the complexes were found to be less flexible and less open in the presence of sucrose than its absence. It is suggested that sucrose contributed greatly to the stabilization of the heat-induced βLG aggregates as they interact with LMP through a preferential exclusion mechanism. Graphical abstract: Weight average molecular characteristics of interacting systems containing βLG (0.3 mg/mL) and LMP (0.1 mg/mL) as studied by HPSEC. Data were analyzed by integrating the chromatographs as peaks 1, 2, 3 and 4. (A) Experimental % Mass Fraction and estimated bound βLG:LMP (w/w); (B) weight average molar mass ([Mw ]); and (C) weight average intrinsic viscosity ([ηw ]). Error bar represents standard deviation of a set of triple RI measurements. Highlights: ∼6.1% native dimeric βLG forms complexes with LMP with preference for the smaller [Mw ]. ∼10.3% heat-treated aggregated βLG forms complexes with LMP of larger [Mw ]. Heat treatment of LMP impeded its binding ability to βLG at βLG:LMP = 3:1 (w/w). Sucrose (∼9%) facilitates the interactions between pre-heated βLG and LMP. Complexes formed between βLG and LMP are more compact in the presence of sucrose.